Chemical Evolution of Antivirals Against Enterovirus D68 through Protein‐Templated Knoevenagel Reactions. Issue 24 (6th May 2021) - Tauber, Carolin; Wamser, Rebekka; Arkona, Christoph; Tügend, Marisa; Abdul Aziz, Umer Bin; Pach, Szymon; Schulz, Robert; Jochmans, Dirk; Wolber, Gerhard; Neyts, Johan; Rademann, Jörg
Abstract: The generation of bioactive molecules from inactive precursors is a crucial step in the chemical evolution of life, however, mechanistic insights into this aspect of abiogenesis are scarce. Here, we investigate the protein‐catalyzed formation of antivirals by the 3C‐protease of enterovirus D68. The enzyme induces aldol condensations yielding inhibitors with antiviral activity in cells. Kinetic and thermodynamic analyses reveal that the bioactivity emerges from a dynamic reaction system including inhibitor formation, alkylation of the protein target by the inhibitors, and competitive addition of non‐protein nucleophiles to the inhibitors. The most active antivirals are slowly reversible inhibitors with elongated target residence times. The study reveals first examples for the chemical evolution of bio‐actives through protein‐catalyzed, non‐enzymatic C−C couplings. The discovered mechanism works under physiological conditions and might constitute a native process of drug development. Abstract : Self‐organized virus killing: Antivirals are generated through aldol condensations catalyzed by the 3C protease of enterovirus D68 and inhibit viral proliferation in infected human cells. Best inhibitors are slow and sticky. The process demonstrates a potentially native mechanism for the evolution of functional bioactive molecules.